Rare genetic variants in the endocannabinoid system genes CNR1 and DAGLA are associated with neurological phenotypes in humans. - Douglas R Smith; Christine M Stanley; Theodore Foss; Richard G Boles; Kevin McKernan (PLoS ONE, 2017)
Rare genetic variants in the core endocannabinoid system genes CNR1, CNR2, DAGLA, MGLL and FAAH were identified in molecular testing data from 6,032 patients with a broad spectrum of neurological disorders. The variants were evaluated for association with phenotypes similar to those observed in the orthologous gene knockouts in mice. Heterozygous rare coding variants in CNR1, which encodes the type 1 cannabinoid receptor (CB1), were found to be significantly associated with pain sensitivity (especially migraine), sleep and memory disorders-alone or in combination with anxiety-compared to a set of controls without such CNR1 variants. Similarly, heterozygous rare variants in DAGLA, which encodes diacylglycerol lipase alpha, were found to be significantly associated with seizures and neurodevelopmental disorders, including autism and abnormalities of brain morphology, compared to controls. Rare variants in MGLL, FAAH and CNR2 were not associated with any neurological phenotypes in the patients tested. Diacylglycerol lipase alpha synthesizes the endocannabinoid 2-AG in the brain, which interacts with CB1 receptors. The phenotypes associated with rare CNR1 variants are reminiscent of those implicated in the theory of clinical endocannabinoid deficiency syndrome. The severe phenotypes associated with rare DAGLA variants underscore the critical role of rapid 2-AG synthesis and the endocannabinoid system in regulating neurological function and development. Mapping of the variants to the 3D structure of the type 1 cannabinoid receptor, or primary structure of diacylglycerol lipase alpha, reveals clustering of variants in certain structural regions and is consistent with impacts to function.